Peran Pengajaran Bahasa Berbasis Drama dalam Meningkatkan Kemampuan Presentasi Peserta Didik - Hera Wahdah Humaira; Syihabuddin Syihabuddin; Vismaia S. Damaianti; Sumiyadi Sumiyadi (Universitas Mulawarman, 2022)
This study aimed to study the effect of drama-based language teaching on students' presentation skills in college. This study used a quasi-experimental method by dividing two groups of participants, namely experimental and control. The samples involved in this study were 100 students from semester 5, divided into 2 groups with the composition of each group of 50 students. The experimental group received a drama-based teaching intervention and was assigned to perform live drama at the end of the semester, while the control group did not. The research results show that drama-based language teaching contributes significantly to students' presentation skills. The improvement in presentation skills is seen in the presentation aspect, namely organization, adaptability, and presentation content. It can be concluded that the intervention of language teaching through drama can improve students' oral language skills or presentation skills. This study implies that in supporting academic activities, students' speaking skills can use drama as an alternative, especially for students who take language studies programs.